The Economics of Price Scissors: Reply - Stiglitz, Joseph E.; Sah, Raaj Kumar (American Economic Review, 1986)
The question of how the funds required for the capital accumulation associated with industrialization are to be raised has a long history. Since the industrial sector is relatively small in the early stages of industrialization, there has been a presumption that funds must primarily come from the agricultural sector. A simple model of a closed socialist economy in which the instruments at the disposal of the government are the terms of trade and the industrial wage, sheds some light on these questions, particularly in the context of the Soviet industrialization debate. In an economy facing binding constraints in external trade, a lowering of the price of the rural good, which reduces the supply of rural surplus available to the urban sector, must be accompanied by a lowering of the urban wage to reduce the demand for the rural good, and hence to balance the supply and demand of the rural good. A virtue of developing a general theoretical framework is that it enables one to isolate those features of the economy which are critical for the issues at hand.